THE EFFECTIVENESS OF JOURNALIST QUESTION TECHNIQUE TO IMPROVE STUDENTS’ WRITING SKILL IN NARRATIVE TEXT (An Experimental Study at Eighth Grade Students of SMP N 19 Semarang in the Academic Year of 2014/2015) (ELT Forum: Journal of English Language Teaching, 2016)
This research is about using Journalist Question technique for teaching writing in junior high school. Journalist Question technique is a technique that can help the students to explore their idea in writing to cover the content of the narrative text. This research that aims to investigate the effectiveness of Journalist Questions technique to improve students’ writing skill in narrative text. The research design used was an experimental research. Tests were used as the instruments to collect the data and information. Before conducting the experiment, try out was given to 33 students of VIII-B to make sure that they were valid and reliable. The researcher used class VIII-D as the experimental group and VIII-C as the control group. Both classes were in the same level, background, and competence. The result of this research showed that the average score of the pre-test in the experimental group was 54.78 and the post-test was 66.42. The improvement on the experimental group was 11.64. While, on the control group, the average score of the pre-test was 53.69 and the post-test was 60.48. The improvement on the control group was 6,73. From the t-test computation of the post-test score, the t-value was higher than t-table (t-value > t-table = 2.083 > 1.998). Therefore, the null hypothesis was rejected and the working hypothesis was accepted. It means that there is a significant difference between the experimental group and the control group. The results indicate that Journalist Question technique technique is effective in improving the writing skill at the eighth graders of SMP Negeri 19 Semarang in the academic year of 2014/2015. It is suggested that the findings of this study could be applied regularly and continously or developed by the English teachers to have a better teaching writing.